Investigation of the Importance of Protein 3D Structure for Assessing Conservation of Lysine Acetylation Sites in Protein Homologs - Jew, Kristen M.; Le, Van Thi Bich; Amaral, Kiana; Ta, Allysa; Nguyen May, Nina M.; Law, Melissa; Adelstein, Nicole; Kuhn, Misty L. (Frontiers in Microbiology, 2022)
Acetylation is a protein post-translational modification (PTM) that can affect a variety of cellular processes. In bacteria, two PTM Nε-acetylation mechanisms have been identified: non-enzymatic/chemical acetylation via acetyl phosphate or acetyl coenzyme A and enzymatic acetylation via protein acetyltransferases. Prior studies have shown that extensive acetylation of Nε-lysine residues of numerous proteins from a variety of bacteria occurs via non-enzymatic acetylation. In Escherichia coli, new Nε-lysine acetyltransferases (KATs) that enzymatically acetylate other proteins have been identified, thus expanding the repertoire of protein substrates that are potentially regulated by acetylation. Therefore, we designed a study to leverage the wealth of structural data in the Protein Data Bank (PDB) to determine: (1) the 3D location of lysine residues on substrate proteins that are acetylated by E. coli KATs, and (2) investigate whether these residues are conserved on 3D structures of their homologs. Five E. coli KAT substrate proteins that were previously identified as being acetylated by YiaC and had 3D structures in the PDB were selected for further analysis: adenylate kinase (Adk), isocitrate dehydrogenase (Icd), catalase HPII (KatE), methionyl-tRNA formyltransferase (Fmt), and a peroxide stress resistance protein (YaaA). We methodically compared over 350 protein structures of these E. coli enzymes and their homologs; to accurately determine lysine residue conservation requires a strategy that incorporates both flexible structural alignments and visual inspection. Moreover, our results revealed discrepancies in conclusions about lysine residue conservation in homologs when examining linear amino acid sequences compared to 3D structures.